The strategies of the players of an RPG game in the context of water resources management: an analysis based on the discourse of the collective subject - Mota, Fernanda Pinto; Born, Miriam; Aguiar, Marilton; Adamatti, Diana Francisca (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Games are widely used in Education because they enable analyzing strategies that come close to reality. In Environmental Education, the game helps understand a particular theme and allows the observation of the approach from a player’s perspective. In this way, each person can develop strategies that s/he considers relevant in the game. This study analyzes players’ strategies in an RPG (Role-Playing Game) in water resources. This work's main contribution is an empirical and qualitative study on individuals’ motivation and how they developed their strategies. As a result, we present the analysis of the players' habits through a semi-structured interview, which resulted in a set of speeches based on the Collective Subject Discourse (CSD).